2019
DOI: 10.1111/wrr.12778
|View full text |Cite
|
Sign up to set email alerts
|

A bioengineered living cell construct activates metallothionein/zinc/MMP8 and inhibits TGFβ to stimulate remodeling of fibrotic venous leg ulcers

Abstract: Venous leg ulcers (VLU) represent a major clinical unmet need, impairing quality of life for millions worldwide. The bioengineered bilayered living cell construct (BLCC) is the only FDA‐approved therapy demonstrating efficacy in healing chronic VLU, yet its in vivo mechanisms of action are not well understood. Previously, we reported a BLCC‐mediated acute wounding response at the ulcer edge; in this study we elucidated the BLCC‐specific effects on the epidermis‐free ulcer bed. We conducted a randomized control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 43 publications
3
22
0
Order By: Relevance
“…Compared with the human normal wounds at the inflammatory phase (NW1) or the proliferative phase (NW7), we found that the expression of miR-19a/b and miR-20a were significantly downregulated in all the three major types of chronic wounds, that is, VU, DFU, and PU, which may contribute to sustained inflammation and impaired healing there. Interestingly, recent studies have revealed beneficial effects of converting chronic wound microenvironment to a healing milieu similar to that in an acute wound (Stone et al, 2020(Stone et al, , 2017. In line with this, our study suggested that the replenishment of miR-19b and miR-20a in wounds with a deficiency of these miRs has therapeutic potential.…”
Section: Discussionsupporting
confidence: 86%
“…Compared with the human normal wounds at the inflammatory phase (NW1) or the proliferative phase (NW7), we found that the expression of miR-19a/b and miR-20a were significantly downregulated in all the three major types of chronic wounds, that is, VU, DFU, and PU, which may contribute to sustained inflammation and impaired healing there. Interestingly, recent studies have revealed beneficial effects of converting chronic wound microenvironment to a healing milieu similar to that in an acute wound (Stone et al, 2020(Stone et al, , 2017. In line with this, our study suggested that the replenishment of miR-19b and miR-20a in wounds with a deficiency of these miRs has therapeutic potential.…”
Section: Discussionsupporting
confidence: 86%
“…In addition, several processes such as angiogenesis, ECM remodelling, and induction of stem cells are hindered. Chronic wounds were also continuously inflamed, as was demonstrated by several studies [308,[314][315][316][317][318]. However, the underlying cellular and molecular mechanisms of impaired wound healing are not yet fully understood.…”
Section: Wound Pathophysiologymentioning
confidence: 98%
“…In venous leg ulcers (VLU) in particular, the wound bed is histopathologically characterized by disorganized ECM, marked fibrosis, and chronic inflammatory infiltrates, all of which contribute to impaired healing; in fact, increased presence of dense fibrosis and high mature collagen levels in VLUs correlate with poor healing outcomes in the clinical setting [ 74 ]. Using microarray profiling, our group reported enrichment of inflammatory response and fibrogenetic pathways in non-healing VLU [ 13 ], corresponding to the histological findings of disorganized ECM, fibrosis, and chronic inflammation [ 73 , 74 , 75 ]. Specifically, we observed enrichment of collagens and secreted matricellular proteins in conjunction with upregulation of fibronectin (FN1), tenascin (TNC), osteopontin (SPP1), connective tissue and hepatocyte growth factors (CTGF, HGF), and PAI-1 (SERPINE1).…”
Section: Fibrosing Disorders Of the Skinmentioning
confidence: 99%
“…We extended our findings in a randomized controlled post-marketing clinical trial examining the mechanism of action of a bioengineered bilayered cellular construct (BLCC), a commercial skin substitute with demonstrated efficacy in promoting VLU closure. BLCC application triggered an acute wound healing response at the ulcer edge to reverse chronic inflammation [ 76 ] while coordinately stimulating remodeling of the ulcer bed, as evidenced by decreased expression of profibrotic TGFß1 gene targets, increased levels of TGF-ß inhibitor decorin, and endogenous release of matrix metalloproteinase (MMP)-activating zinc to stimulate antifibrotic remodeling [ 13 ]. As such, the development and application of anti-fibrotic therapies represent a novel treatment approach for VLUs and other non-healing ulcers.…”
Section: Fibrosing Disorders Of the Skinmentioning
confidence: 99%
See 1 more Smart Citation